RANCANG BANGUN SISTEM PENYUSUNAN PORTOFOLIO DAN CV BERBASIS VISUAL BUILDER: STUDI KASUS MAHASISWA UNWAHA - Luky Widyastutik; Primadi Airlangga (KH. A. Wahab Hasbullah University, 2020)
The problem of students who will and have graduated from college is in terms of job search, among others, their layman in making a CV. To solve the problem was created a career center website with CV category. A website where their personal data can be filled into the template that has been provided so as to make it easier for them to apply for a job. So the research design portfolio system and cv was developed as well as helping the campus to record its students, which is not only student personal data but also the skills possessed by students. Design this system based on a visual builder that is able to process data and facilitate automatic storage.